Portable Hovercraft Concept 3.0 - Ahmad Sharainon, Ahmad Muizzuddin; Saifuddin, Danial Haqiemi; Khairol Affandi, Aniq Harith; Asril Rajo Mantari, Encik Muhammad Hanafi (Multidisciplinary Applied Research and Innovation, 2022)
Hovercraft types of vehicles that is lifted above the surface of land or water by an air cushion created by downward-directed fans. It also classified as Air Cushioned Vehicles (ACV) owing to their capacity to travel through a cushion or skirt filled with air that causes the board to hover above the ground. This concept utilizes single propeller that can provide sufficient lift and also propel the hovercraft. There are 5 main part of this portable hovercraft which is chassis, fan, duct, skirt, and engine. A chassis was made from the Aluminum Alloy 6061. It is the main part of this project. Umbrella mechanism were used to make the portable chassis. It is easy to fold and unfold it. Next, the propeller is made from wood and connected directly to the engine, without the needs for belts or chain for power transmission. The 5-blade design with 35 pitching angle is used to propel forward and lift the hovercraft. Fabric skirting from neoprene coated nylon was used to contain air laterally and is shaped like an open tube with very low air pressure coming from the propeller. Neoprene coated nylon has its durability higher endurance from being scratch for a long period of time. To increase the propeller's efficiency, a fan with a non-rotating nozzle called a duct was constructed from fiber. Additionally, it serves as a replacement for the rudder, resulting in increased thrust in a more compact package. A four-stroke petrol engine powers with 6.5HP power was used in this project. In general, our purpose is to design and manufacture a portable hovercraft that can move and hover while weighing a 60KG human.